2015
DOI: 10.1039/c5ra05115k
|View full text |Cite
|
Sign up to set email alerts
|

Largely reinforced polyurethane via simultaneous incorporation of poly(lactic acid) and multiwalled carbon nanotubes

Abstract: In this study, we simultaneously introduced both poly(lactic acid) (PLA) and multiwalled carbon nanotubes (CNTs) into the polyurethane (PU) matrix via melt blending, to achieve balanced mechanical properties and good conductivity. Different contents of PLA (0-30 wt%) and CNTs (0-3.0 wt%) were used in this work. A significant improvement in tensile strength at 300% strain and Young's modulus were observed, which could not be obtained by incorporating either PLA or CNTs with PU separately. Particularly, the tern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…PU elastomers (PUe) have attracted much attention because of their high ductility, toughness, and good stability. , However, low stiffness and low strength limit their application, which is about 10 MPa for the Young’s modulus and 10–25 MPa for tensile strength. A general strategy to reinforce PUe is by blending them with other polymers such as polycaprolactone and poly­(acrylic acid) or by incorporating inorganic/organic fillers, including graphene, carbon nanotubes (CNTs), et al , However, due to aggregation of the fillers, the improved modulus and strength at high filler content are also accompanied by reduction of ductility and toughness. , To facilitate a better dispersion, in situ polymerization of monomers that possess reactive functional groups is another approach. Lignin, with abundant phenolic and aliphatic hydroxyl groups that could readily react with isocyanates to form urethane linkage, is a good candidate for preparation of biobased high value-added products, , especially for PU materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PU elastomers (PUe) have attracted much attention because of their high ductility, toughness, and good stability. , However, low stiffness and low strength limit their application, which is about 10 MPa for the Young’s modulus and 10–25 MPa for tensile strength. A general strategy to reinforce PUe is by blending them with other polymers such as polycaprolactone and poly­(acrylic acid) or by incorporating inorganic/organic fillers, including graphene, carbon nanotubes (CNTs), et al , However, due to aggregation of the fillers, the improved modulus and strength at high filler content are also accompanied by reduction of ductility and toughness. , To facilitate a better dispersion, in situ polymerization of monomers that possess reactive functional groups is another approach. Lignin, with abundant phenolic and aliphatic hydroxyl groups that could readily react with isocyanates to form urethane linkage, is a good candidate for preparation of biobased high value-added products, , especially for PU materials.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, low stiffness and low strength limit their application, which is about 10 MPa for the Young's modulus and 10−25 MPa for tensile strength. 3−6 A general strategy to reinforce PUe is by blending them with other polymers such as polycaprolactone and poly(acrylic acid) or by incorporating inorganic/organic fillers, including graphene, carbon nanotubes (CNTs), et al 7,8 However, due to aggregation of the fillers, the improved modulus and strength at high filler content are also accompanied by reduction of ductility and toughness. 4,6 To facilitate a better dispersion, in situ polymerization of monomers that possess reactive functional groups is another approach.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[17,18] Several research have reported the effect of CNTs on the foaming behaviors of biodegradable nanocomposites. [4,[19][20][21][22] In one of our previous works, a simple, green foaming way was utilized to fabricate PLA/CNTs nanocomposite foam with an ultra-high volume expansion ratio (VER) of 49.6. [4] Furthermore, Huang et al prepared PBS/CNTs/PTFE ternary composite foam with admirable electrical conductivity (σ) via using "ball milling" and supercritical CO 2 (scCO 2 ) foaming processing.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Therefore, extensive works have been done to incorporate graphene into various polymers and investigate the properties of the formed composites. [12][13][14][15][16] The dispersion state of graphene plays a vital role in the nal properties of the composites. Small addition could signicantly reinforce many properties of host polymers if in which graphene dispersed uniformly.…”
Section: Introductionmentioning
confidence: 99%